Tinjauan Yuridis Wanprestasi Dalam Perjanjian Sewa Menyewa Rumah: (Studi Putusan Nomor 177/Pdt.G/2019/PN.Jkt.Utr) - Robbi Firly Firgiyabi Mahlafi (JOURNAL SAINS STUDENT RESEARCH, 2023)
A lease is an agreement whereby one party binds himself to give another party the enjoyment of an item for a certain period of time and with the payment of a price which the latter party is willing to pay. The rights and obligations of the parties in the rental agreement. The rights of the renting party are the rights that will be received by the renting party. The renting party has the right to rent which must be paid by the lessee at a certain time in accordance with the rental agreement. The party who rents out has the right to pandbeslag, which is a confiscation carried out by the court at the request of the renter, such as regarding household furniture in the house being rented out if the tenant is in arrears on the rent for the house to be auctioned off if the tenant does not pay the rent arrears in full. The renting party has the right to request cancellation of the agreement and compensation. The lessor's right is to hand over the leased object to the lessee, maintain the leased object in such a way that the object can be used for its intended purpose. The rental agreement ends in default before the term of the agreement expires, that is, the rental agreement can end automatically at a certain time, after being terminated by observing a certain grace period. Even though a lease is a consensual agreement, the law provides a distinction between a written lease and an oral lease. The legal consequences of a breach of contract in a housing rental agreement if there has been a previous rental agreement, then if one of the parties breaks their promise (default) by not fulfilling the contents of the agreement, then the breaking party (in this case the tenant) can be sued civilly on the basis of breach of contract as regulated in Article 1243 of the Civil Code (Civil Code). Article 1267 of the Civil Code, regulates several things that can be sued/sought by the Owner from the Party who is in default, namely: (1) Fulfillment of the Agreement, (2) Fulfillment of the Agreement with Compensation, (3) Compensation, (4) Cancellation of Agreement, (5) Cancellation of Agreement with compensation.